CARDI Communications Guides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
CARDI Communications Guides - 1 Style guide for technical editors prepared by Don Walmsley 1996 29pp ISBN 976 617 003 7